Dual antiplatelet therapy duration after percutaneous coronary intervention with contemporary drug-eluting stents: A systematic review and network meta-analysis of randomized trials - Admire Hlupeni; Mehran Jalilzadehbinazar; Rayvlin J. Liceralde; Hussain A. M. Khan; Ravi Donepudi; Shilpkumar Arora (PLOS One, 2026)
Background Despite widespread adoption of abbreviated (